ANALISIS RETORIKA ARISTOTELES PADA KAJIAN ILMIAH MEDIA SOSIAL DALAM MEMPERSUASI PUBLIK - Dhia, Rifqi Nadhmy; Pramesthi, Jasmine Alya; Irwansyah, Irwansyah (Linimasa : Jurnal Ilmu Komunikasi, 2021)
In order to build public awareness of the current crisis, many persuasive messages are disseminated through social media. Public communication is considered to be utilizing the power of YouTube as a popular social media platform in effectively communicating crisis through persuasive messages. In previous research the three aspects of ethos, pathos, and logos have been found as evidence of rhetoric in conveying persuasive messages made by YouTubers. The implications of study about rhetoric continue to develop today. This study aims to review other Aristotle’s rhetoric concepts that has not been analyzed in previous studies. The research used qualitative exploratory methods including in-depth interviews and observations. The sample size of participants in this study follows the concept of saturation. The study uncovered that there are two other concepts regarding rhetorical theory by Aristotle in this study — the type of rhetoric used and the five rhetorical canons when the speaker conveys a message. The researcher suggests further research to explore the concept of rhetorical inartistic evidence that is outside the rhetoric element brought by the speaker, so that the study can be discussed more comprehensively.